The Risk Factors in Early Failure of Dental Implants: a Retrospective Study - Hassan Mohajerani; Roozbeh Roozbayani; Shahram Taherian; Reza Tabrizi (Shiraz University of Medical Sciences, 2017)
Statement of the Problem: Despite the low failure rate of dental implants, recognition of the risk factors can enhance the predictability of failure. Purpose: The aim of this study was to evaluate the risk factors for early implant failure. Materials and Method: This retrospective cohort study was conducted on two groups of patients, the patients with a failed implant before loading and those without a failed implant. Age, gender, implant type, implant surface, implant length, bone type, type of surgery (one- or two-stage) and immediate (fresh socket) or delayed placement of implant were the variables to be assessed in this study. Results: Out of the 1,093 evaluated implants, 73 cases (6.68%) failed in early stages. The two groups were significantly different in terms of implant surface, fresh socket placement, prophylactic use of antibiotics, and bone density (p< 0.05). Age, gender, implant height, implant type (cylindrical or tapered) and one-stage or two-stage placement were not significantly different between the two groups (p> 0.05). Conclusion: It seems that prophylactic antibiotic therapy, implant surface, bone density and placement in fresh extraction socket may contribute to dental implant failure.